2137 Hard Red Winter Wheat - Sears, Rollin G.; Martin, T. Joe; Shroyer, James P. (My University, 1996)
An informational publication about 2137, a new hard red winter wheat variety developed cooperatively by the Kansas Agricultural Experiment Station and the Agricultural Research Service, United States Department of Agriculture.
L906_1996-04
Keywords: L906; Crops; L